The likely economic impact of increasing investment in wind on the Island of Ireland - Conor Devitt; Seán Diffney; John Fitz Gerald; Seán Lyons; Laura Malaguzzi Valeri (The Economic and Social Research Institute (ESRI), 2009)
Like most countries Ireland faces the double target of decreasing emissions and keeping energy costs low to maintain competitiveness of the economy. The two goals are not always compatible. This study measures the effect of increasing wind in electricity generation on the total electricity costs for the Island of Ireland for the year 2020 under a variety of scenarios on fuel and carbon costs, generating plant portfolio mixes and electricity demand growth. We find that with high levels of interconnection 6000MW of installed wind capacity are likely to reduce overall costs, especially if the price of natural gas stays high. The sensitivity of the results to the level of interconnection suggests that it is important for interconnection to be operated and governed as efficiently as possible. We also find that the deregulated all-island system will face major challenges moving into the future since returns to traditional fossil-fuelled plants might not be sufficient to create new (needed) investment when wind penetration is high.
Keywords: 330; electricity; interconnection; Ireland; wind generation; returns to investment; Windenergieanlage; Return on Investment; Energiepreis; Energiekonsum; Irland